TEKNOLOGI DIGITAL MEMEDIASI DAMPAK STRATEGI BISNIS TERHADAP KINERJA UMKM DI NUSA TENGGARA BARAT - Armiani Armiani; Basuki Basuki; Noorlailie Suwarno (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
The use of digital technology (e-commerce and social media) can increase the influence business strategy on the MSME performance. This study aims to examine digital technology in mediating the effect business strategy on the MSME performance. This study uses a quantitative approach with an explanatory research design, observation and questionnaire methods, with purposive sampling on halal certified and labeled food products, MSME that transact business using e-commerce and social media 2017-2019 in NTB, a sample 650 MSME with a response rate 536 MSME. The analysis tool used is SmartPLS. The findings show that digital technology partially mediates business strategy on the performance MSME. Digital technology is an intermediary variable that is able to be competitive in the global market, because MSME can do online marketing, so that their products can be recognized and can increase sales. The business strategy applied is the cost leadership strategy in terms; dominant commodity produc, production process using traditional tools, new product development, at least cooperation with resellers. Financial performance has increased sales and operating profit, non-financial performance has increased; Product quality, product quality, production target services and provide information about effectiveness, the use of digital technology in business strategies to improve the MSME performance.